2001
DOI: 10.1086/321442
|View full text |Cite
|
Sign up to set email alerts
|

A Black Hole in the Superluminal Source SAX J1819.3−2525 (V4641 Sgr)

Abstract: Spectroscopic observations of the fast X-ray transient and superluminal jet source SAX J1819.3[2525 (V4641 Sgr) reveal a best-Ðtting period of days and a semiamplitude of P spect \ 2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
269
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(307 citation statements)
references
References 33 publications
31
269
7
Order By: Relevance
“…In the interim, the abundance excesses for X-ray absorption edges in GRS 1915]105 can be contrasted with the discovery of abundance anomalies in the optical spectra of companion stars in the microquasars GRO J1655[40 and V4641 Sgr (Israelian et al 1999 ;Brown et al 2000 ;Orosz et al 2001). In the latter cases, the overabundances of aprocess elements, but not the Fe group, have led to the hypothesis that the companion star captured supernova or hypernova ejecta is related to the formation of the black hole.…”
Section: Discussionmentioning
confidence: 99%
“…In the interim, the abundance excesses for X-ray absorption edges in GRS 1915]105 can be contrasted with the discovery of abundance anomalies in the optical spectra of companion stars in the microquasars GRO J1655[40 and V4641 Sgr (Israelian et al 1999 ;Brown et al 2000 ;Orosz et al 2001). In the latter cases, the overabundances of aprocess elements, but not the Fe group, have led to the hypothesis that the companion star captured supernova or hypernova ejecta is related to the formation of the black hole.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be interesting to analyze other elements such as O, Mg, and C, which are enhanced in many of the model computations in Tables 4 and 5, even at high mass cuts. We note that Orosz et al (2001) have also found overabundances (by a factor 2-10 with respect to solar) of some of these elements in the secondary star of the LMXB system J1819.3À2525 (V4641 Sgr).…”
Section: Evv Olutionary Scenariomentioning
confidence: 63%
“…We also speculate that Fe may be overabundant (relative to solar) by a factor of a few in this source. Orosz et al (2001) report that N and Ti may be overabundant by a factor of 10, Mg by a factor of 7, O by a factor of 3, and Ca by a factor of 2.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, advectiondominated accretion flow (ADAF) models for transient systems (e.g., Esin, McClintock, & Narayan 1997) Orosz et al 2001). Hjellming et al (2000) mond ≤ 12.31 itored the outburst in radio and found jets expanding at apparently superluminal velocities; V4641 Sgr is therefore termed a "microquasar."…”
mentioning
confidence: 99%